Management of advanced non‐melanoma skin cancers using helical tomotherapy. (6th April 2013) - Kramkimel, N.; Dendale, R.; Bolle, S.; Zefkili, S.; Fourquet, A.; Kirova, Y.M.
Abstract Background Helical tomotherapy (HT) is a relatively new method of radiotherapy, the main advantages of which are an increase of irradiation dose on the target tumour volume and best protection of adjacent organs at risk. Objective To provide an accurate evaluation of efficiency and tolerance of HT on different kinds of non‐melanoma skin tumours. Patients and methods We analysed, retrospectively, 25 patients (pts) who were treated with HT for advanced non‐melanoma skin cancers. We studied the characteristics of patients and tumours, associated treatments, characteristics, efficacy and tolerance of HT treatment. Results Eight had basal cell carcinoma, Eight had cutaneous squamous cell carcinoma, five Merkel cell carcinoma and four adnexal carcinoma. The median age was 75 years (range 51–89). The median follow‐up was 12 months. HT was used because of incomplete excision (n = 12), lymph node involvement (n = 6), non‐operable lesions (n = 4) and high risk of relapse (n = 4). The delivered dose for the tumour bed was between 50 and 70 Gy and for the lymph node it was between 50 and 64 Gy. There was no grade III–IV adverse event, except one grade III mucositis. Fourteen pts suffered from limited toxic effects 6 months after the end of the treatment, mainly loss of eyebrow and teared eye. Complete remission was noticed for 22 pts (88%); one pt had progressive disease and two pts died. Conclusion HT is an effective option for advanced non‐melanoma skin cancers as radical treatment or in association with surgery. Early and late toxicity and cosmetic results are acceptable.